Bartonella native valve endocarditis: the first brazilian case alive and well - Lamas,C. (2007)
Bartonella is an important cause of blood culture-negative endocarditis in recent studies. Seroprevalence studies in the States of Minas Gerais and Rio de Janeiro have shown Bartonella IgG positivity around 14% in healthy adults and 40% in HIV seropositive adults, respectively. A case report of a 46-year-old white male with moderate aortic regurgitation (AR) due to rheumatic heart disease (RHD), admitted due to worsening heart failure, is presented. Clinical features were apyrexia, anemia, polyclonal hypergammaglobulinemia, hematuria and splenomegaly. He was submitted to surgery due to worsening AR. Histopathology of the excised valve showed active bacterial endocarditis and underlying RHD. Routine blood cultures were negative. Indirect immunofluorescence (IFI) assays for Coxiella burnetii were non-reactive. Bartonella henselae IgG titer was 1:4096 prior to antibiotics and 1:512 14 months after treatment. History of close contact with a young cat during the months preceding his admission was elicited.